The geological factors responsible for the compartmentalisation and the heterogeneity phenomena: a case study from the lower Zubair reservoir in Bahrah Field, Kuwait - Najeeb S. Aladwani; Abdulmohsen Alenezi (All Earth)
This study investigates the effect of compartmentalisation in the Lower Cretaceous Zubair Formation in the Bahrah Field in Kuwait, with proven plays’ success ranging from 50 to 60% due to irregular trapping configurations and fluid retention resulting from reservoir compartmentalisation and heterogeneity. An integrated analysis was conducted, including facies mapping, core data, sedimentological and petrographic assessments, pressure measurements and fluid contacts correlated with the structure map that was subjected to cross-fault juxtaposition analysis to test fault sealing capability. It’s found that the main reservoir units Z10 and Z23 are trapped on the upper down-dip side of the Bahrah Anticline by a set of NW-SE trending faults exhibiting effective sealing. Vertically, the reservoirs are sealed by internal Zubair shales. The Z10 unit is highly compartmentalised by strong lateral sealing from the Ratawi shale, while the Z23 unit experiences some hydrocarbon leakage through fault planes. Core data indicate reservoirs have an average porosity of 14.2% (7.6–20%), shale volume of 12.8% (7.2–20.3%), water saturation of 42.2% (19.5–100%) and permeability of 1080 mD (.01–6180 mD). Pressure measurements, fluid contacts and sedimentological analysis support lateral heterogeneity. The traps are a combination of structural and stratigraphic mechanisms related to the fluvio-deltaic depositional environment and subsequent deformation.